HUBUNGAN KEPUASAN KERJA DENGAN KINERJA KARYAWAN PADA FRONT OFFICE DEPARTEMENT DI HOTEL ROCKY PLAZA PADANG - Fajri, Nurul; Elida, Elida; Abrian, Youmil (Journal of Home Economics and Tourism, 2015)
The purpose of research is to analyze the relationship between jobsatisfaction with staff front office performance in Rocky Plaza Hotel Padang. Thisstudy is a descriptive correlational study. The population numbered 30 people ofstaff front office department, Informant selection techniques in the study usingsaturated sampling technique for 30 people of staff front office department, datacollection techniques with a structured questionnaire based on Likert scale thathas been tested for validity and reliability. Based on the survey results revealedthe percentage of incoming job satisfaction overall categorized good (90%), stafffront office performance in Rocky Plaza Hotel Padang overall as enough(40%).The results showed that there between job satisfaction with staff frontoffice performance in Hotel Rocky Plaza Padang is didn’t have a Positive andsignificant relationship, it means if the job satisfaction good, the performance ofstaff front office would be good also.Keywords: Leadership and Performance1